(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The Naryn region in the high mountain valley of the Inner Tien Shan, due to its geographical location, the natural distribution of plants includes a particularly biologically diverse environment. The Salkyn-Tor State Natural Park, distinguished by its unique nature and harsh climatic conditions, is limited to the alpine zone, since most of the territory of the Salkyn-Tor State Natural Park is located at an altitude of 2500-4000 m above sea level. Therefore, the types of plants change, the physiological processes also change, and characteristic petrophilic plants appear